TUMPAHAN MINYAK MONTARA DAN ANCAMAN TERHADAP KEBERLANJUTAN RUMPUT LAUT - Aghna Mau'ila Darmatina; Ayuni Putri Nabila; Karina Lusiana; Ralina Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Montara oil spill that occurred in 2009 in the Timor Sea is considered one of the worst oil spills in the world due to the oil pollution problems it caused to Indonesian seas, especially in East Nusa Tenggara (NTT). This Sabidurism aims to investigate in detail the ecosystem impact and socio-economic impact of Montara on seaweed farming activities in the affected areas. In this case, the collection method involves studying the literature, analyzing secondary data, and analyzing environmental reports from various relevant sources. From the descriptive analysis, it was concluded that in addition to oil pollution, the impact on the ecosystem is considerable, reducing seaweed cultivation yields, and losing the main source of income for farmers. This results in more damage and losses to the community, exacerbating an already bad situation. This research is useful in strengthening the development of more proactive regulatory proposals for environmental protection. For prevention and the need for a mechanism to respond to environmental crises between countries, especially for large-scale oil spill emergencies.